The Sublimation of Ki Hajar Dewantara's Values in Islamic Religious Education at Malang Elementary School - Ahmad Khoirul Mustamir; Ahmad Nur Ismail; Moch Mukhlison (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
Religious character plays a significant role in shaping students' personalities. By integrating religious values into the educational process, students are encouraged to behave positively. Therefore, Islamic Religious Education (PAI) teachers hold a key responsibility in ensuring the success of religious character development in schools through the implementation of well-designed strategies. However, in practice, PAI teachers often face several challenges, such as limited learning time and inadequate facilities. This study aims to provide a comprehensive description of the foundation, implementation, and implications of the strategies used by Islamic Religious Education (PAI) teachers in shaping the religious character of students at SDN Malang. To achieve this objective, the researcher employed a qualitative approach with a field research design. Data were collected through several techniques, including observation, interviews, and documentation. Meanwhile, The data analysis process followed the steps proposed by Miles and Huberman, namely condensing interview data, documentation, and observations to draw conclusions in line with the research focus. Conclusions were drawn using propositional sentences to emphasize theoretical contributions. The results showed that: the foundations used are religious, curriculum, psychological, and sociological foundations. While the implementation with role model, giving understanding, habituation, punishment, giving gifts. The implication is that students show positive changes in terms of discipline in worship, respect for teachers and parents, and enthusiasm for participating in religious activities.